2019
DOI: 10.1016/j.jctube.2019.100102
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis-specific cytokine biomarkers for the diagnosis of childhood TB in a TB-endemic setting

Abstract: The tuberculin skin test and interferon-gamma release assays have limitations in diagnosing tuberculosis (TB), particularly in children. This study investigated the performance of candidate M. tuberculosis-specific cytokine biomarkers for TB in children in a TB-endemic setting. A total of 237 children with a household contact with smear-positive pulmonary TB were recruited. Importantly, a group of children with illnesses other than TB (sick controls) was included to assess specificity.Median IFN-ɣ, IL-1ra, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
(48 reference statements)
3
13
1
Order By: Relevance
“…The serum biosignature consisting of 16 proteins (APRIL/TNFSF13, sCD30/TNFRSF8, chitinase 3-like 1, sIL-6Rα, IL-8, IL-11, IL-12(p70), IL-19, IL-28A/IFN-λ2, LIGHT/TNFSF14, MMP-1, MMP-2, MMP-3, OPN, PTX-3, TWEAK/TNFSF12) was found informative for the differentiation between the TB and HC groups, while the panel of 15 proteins (IL-6, APRIL/TNFSF13, sCD30/TNFRSF8, gp130/sIL-6β, IL-2, sIL-6Rα, IL-8, IL-29/IFNλ1, IL-35, MMP-2, MMP-3, OPN, PTX-3, sTNF-R2, TWEAK/TNFSF12) distinguished the HC group from the LTBI cohort. Currently, a number of studies have demonstrated a potential of blood-derived host protein biomarkers in the diagnosis of active TB [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. A 6-marker serum protein biosignature consisting of CRP (c-reactive protein), IFN-γ, IP-10 (human interferon-inducible protein 10), CFH (complement factor H), Apo-AI (apolipoprotein AI), and SAA (serum amyloid A) showed a potential in the diagnosis of childhood tuberculous meningitis48.…”
Section: Discussionmentioning
confidence: 99%
“…The serum biosignature consisting of 16 proteins (APRIL/TNFSF13, sCD30/TNFRSF8, chitinase 3-like 1, sIL-6Rα, IL-8, IL-11, IL-12(p70), IL-19, IL-28A/IFN-λ2, LIGHT/TNFSF14, MMP-1, MMP-2, MMP-3, OPN, PTX-3, TWEAK/TNFSF12) was found informative for the differentiation between the TB and HC groups, while the panel of 15 proteins (IL-6, APRIL/TNFSF13, sCD30/TNFRSF8, gp130/sIL-6β, IL-2, sIL-6Rα, IL-8, IL-29/IFNλ1, IL-35, MMP-2, MMP-3, OPN, PTX-3, sTNF-R2, TWEAK/TNFSF12) distinguished the HC group from the LTBI cohort. Currently, a number of studies have demonstrated a potential of blood-derived host protein biomarkers in the diagnosis of active TB [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. A 6-marker serum protein biosignature consisting of CRP (c-reactive protein), IFN-γ, IP-10 (human interferon-inducible protein 10), CFH (complement factor H), Apo-AI (apolipoprotein AI), and SAA (serum amyloid A) showed a potential in the diagnosis of childhood tuberculous meningitis48.…”
Section: Discussionmentioning
confidence: 99%
“…TST, QFT assays and T-SPOT.TB assays had sensitivities of ∼80% or below, indicating that approximately one in five children with TBM have a false-negative result when a single immunological test is performed, irrespective of which test is used. Several recent studies, including in patients with TBM, have investigated novel immune-based TB biomarkers in blood that have the potential to improve the diagnosis of TB in children, but additional studies will be required to confirm their findings [ 24 26 ]. Interestingly, our multivariate logistic regression analyses indicate that false-negative TST results were more common in children with more severe TBM.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5 demonstrates this effect graphically by showing that biomarker panels lacking CXCL1, CXCL2, or MMP8 have lower AUC values than the biomarker sets that contain at least 1 of these 3. [31][32][33][34][35][36][37][38][39] . Only one study reported MMP8 performance as a biomarker in children (<25 per diagnostic category) and three studies measured CXCL1 [41][42][43] .…”
Section: Two Different Biomarker Panels Are Identified Using Machine mentioning
confidence: 99%